2010
DOI: 10.1099/jmm.0.015800-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of staphylococcal cassette chromosome mec structures in coagulase-negative staphylococci and relationship to drug resistance

Abstract: The objective of this study was to determine the distribution of staphylococcal cassette chromosome mec (SCCmec) elements in meticillin-resistant coagulase-negative staphylococci (MR-CoNS) isolated from a tertiary-care hospital in Mexico and to examine the relationship to drug resistance. Fifty selected MR-CoNS isolates collected from catheters (n515), blood (n515), bone (n59), bronchial lavage (n52) and urine (n52) and one isolate each from an abscess, cerebrospinal fluid, eye, pleural effusion, synovial flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
26
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
9
26
0
1
Order By: Relevance
“…The impact of antibiotic selective pressure might possibly explain the high prevalence of MR-CoNS carriage. Among the MR-CoNS isolates, S. epidermidis (n= 20/50, 40%) was the predominant species followed by S. haemolyticus (n= 14/50, 28%), S. hominis (n= 10/50, 20%) and S. warneri (n= 6/50, 12%) which was consistent with previous reports [2,17].…”
Section: Discussionsupporting
confidence: 82%
“…The impact of antibiotic selective pressure might possibly explain the high prevalence of MR-CoNS carriage. Among the MR-CoNS isolates, S. epidermidis (n= 20/50, 40%) was the predominant species followed by S. haemolyticus (n= 14/50, 28%), S. hominis (n= 10/50, 20%) and S. warneri (n= 6/50, 12%) which was consistent with previous reports [2,17].…”
Section: Discussionsupporting
confidence: 82%
“…SCCmec IV was predominant in our MRSA strains, a common observation within MR staphylococci isolates in most studies (Ruppe et al, 2009;Garza-Gonzalez et al, 2010;AlBakri et al, 2013;Djoudi et al, 2014). The two MR S. saprophyticus isolates carried SCCmec IVa; however, Söderquist & Berglund (2009) reported that, in this species, SCCmec III was predominant.…”
Section: Discussionmentioning
confidence: 50%
“…This is a rare finding but previously reported in two isolates of MR S. epidermidis and Staphylococcus hominis (Ruppe et al, 2009). However, 19 of 35 isolates were untypeable, a common observation within MRS, underlying the high degree of variability in genetic background of this genus and the great capacity of generating new SCCmec types (Ruppe et al, 2009;Garza-Gonzalez et al, 2010;Urushibara et al, 2011;Al-Bakri et al, 2013). Such findings underline the importance of studying prevalence and composition of SCCmec in MRS, in order to understand and predict the evolution of methicillin (Mongkolrattanothai et al, 2004;Hanssen & Sollid, 2006).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…One of these STs, ST2, was recognized as representing the majority of methicillin-resistant S. epidermidis (MRSE) clinical strains (9,10). ST2 isolates usually harbor the ica operon (11) and can carry different SCCmec types (12).…”
mentioning
confidence: 99%